A method for preparing a perfluorosulfonic acid-covalent organic framework composite membrane for vanadium batteries
The perfluorosulfonic acid-covalent organic frame composite film was prepared by electrochemical peeling and electrodeposition methods, which solved the problem of insufficient vanadium resistance and ion selectivity in the existing membrane in all vanadium flow batteries, and achieved higher battery performance indicators.
Patent Information
- Application Number
- CN202411319668.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-09-23
AI Technical Summary
The existing perfluorosulfonic acid ion exchange membranes have problems with poor vanadium resistance and ion selectivity in all vanadium flow batteries, which is difficult to meet the needs of large-scale applications.
By electrochemical peeling and electrodeposition methods, a perfluorosulfonic acid-covalent organic frame composite membrane was prepared, and the regular pores and positive properties of the covalent organic frame nanosheets were used to improve the proton conductivity and ion selectivity of the membrane.
The hydrophilicity, vanadium resistance and ion selectivity of the membrane are improved, and the coulomb efficiency, voltage efficiency and capacity retention of vanadium batteries are improved.
Smart Images

Figure CN118854400B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of vanadium battery diaphragms, and in particular to a method for preparing a perfluorosulfonic acid-covalent organic framework composite membrane for a vanadium battery. Background Art
[0002] All-vanadium liquid flow battery is a new type of electrochemical energy storage system with the advantages of independent capacity and power, fast response, high efficiency, safety and environmental protection. It is suitable for long-term, large-scale energy storage and plays an increasingly important role in the field of new energy.
[0003] The diaphragm is an important component of the all-vanadium flow battery. Its performance, stability and production cost are one of the important factors affecting the large-scale application of vanadium batteries. The perfluorosulfonic acid ion exchange membrane currently used realizes proton conduction through micelle channels. However, it has a large ion transmission channel, so it has problems such as poor vanadium resistance and ion selectivity. An effective modification method is needed to further improve the performance and stability of the perfluorosulfonic acid membrane.
[0004] Covalent organic framework is a crystalline organic porous polymer material, which is composed of small molecules connected by covalent bonds. It has highly regular pores and periodic structure in space, and is an ideal material for separation membrane. However, the covalent organic framework synthesized by traditional solvothermal method usually exists in the form of powdered solid, which is difficult to directly process and use for the preparation of thin-layer membrane structure, and the processability and film-forming property are poor. Therefore, it is urgent to develop a simple and efficient way to convert the powdered covalent organic framework into a thin film structure and composite it with perfluorosulfonic acid membrane, so as to improve the comprehensive performance of all-vanadium liquid flow battery. Summary of the invention
[0005] The present invention provides a method for preparing a perfluorosulfonic acid-covalent organic framework composite membrane for a vanadium battery. The electrochemical stripping and electrochemical deposition of covalent organic framework powder are achieved by a one-step method to prepare a perfluorosulfonic acid-covalent organic framework composite membrane, thereby improving the performance of the vanadium battery. Specifically, by applying an electric field, under the combined action of an electric field and a weak oxidant, the insoluble cationic covalent organic framework powder of the anode is stripped into a few layers of covalent organic framework nanosheets, and dispersed in a solvent. At the same time, the stripped cationic covalent organic framework nanosheets move in a directional manner in the solvent under the action of the electric field force, forming an electrodeposition effect, and forming a complete and defect-free cationic covalent organic framework separation layer on the surface of the cathode finished film. The modified perfluorosulfonic acid-covalent organic framework composite membrane has better hydrophilicity, enhanced positive charge and smaller effective pore size, improves the vanadium resistance, ion selectivity and proton conductivity of the membrane, and thus improves the coulomb efficiency, voltage efficiency and capacity retention rate of the vanadium battery.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A method for preparing a perfluorosulfonic acid-covalent organic framework composite membrane for a vanadium battery comprises the following steps:
[0008] S1, adding 2 to 10 parts by mass of cationic amine monomers, 3 to 15 parts by mass of aldehyde monomers, 0.5 to 2 parts by mass of catalysts and 100 to 1000 parts by mass of solvents into a reaction kettle, ultrasonically dispersing for 10 to 30 minutes, bubbling with nitrogen and sealing, and then solvothermally reacting at 90 to 120° C. for 24 to 72 hours, and washing and drying to obtain a cationic covalent organic framework powder;
[0009] S2. Add 0.2 to 2 parts by mass of an oxidant and 0.2 to 2 parts by mass of a solvent to 1 to 15 parts by mass of a covalent organic framework powder, grind in a mortar for 5 to 30 minutes to obtain a slurry, apply the slurry to the surface of a graphite electrode, heat and dry at 60 to 100° C. for 10 to 30 minutes, and then insert the graphite electrode into an electrolytic cell as an anode; fix the finished perfluorosulfonic acid ion exchange membrane on the surface of an indium tin oxide conductive glass, and insert the slurry into the electrolytic cell as a cathode;
[0010] S3, adding a solvent to the electrolytic cell until the liquid level is higher than the two electrodes, applying a DC voltage between the two electrodes, performing an electrochemical reaction, and realizing the electrostripping and electrodeposition of the covalent organic framework in one step;
[0011] S4. After the reaction is completed, the membrane is removed from the negative electrode surface, and after cleaning and drying, a perfluorosulfonic acid-covalent organic framework composite membrane is obtained.
[0012] Preferably, in step S1, the cationic amine monomer is selected from one of triaminoguanidine hydrochloride, ethidium bromide, 1,4-diamino-2-trimethylaminomethoxybenzene hydrochloride, trimethylaminopropoxyterephthaloylhydrazide hydrochloride and 1,1'-bis(4-aminophenyl)-[4,4'-bipyridine]-1,1'-diammonium chloride.
[0013] Preferably, in step S1, the aldehyde monomer is selected from one of 1,3,5-trialdehyde benzene, 2,4,6-tris(4-aldehyde phenyl)pyridine, 2,4,6-trialdehyde pyran, tris(4-aldehyde biphenyl)amine and 2,4,6-tris(4-aldehyde phenyl)-1,3,5-triazine.
[0014] Preferably, the catalyst in step S1 is selected from one of acetic acid solution, trichloroacetic acid and scandium trifluoromethanesulfonate.
[0015] Preferably, the solvent in step S1 is selected from one of deionized water, dioxane, mesitylene, N,N-dimethylformamide and NN-dimethylacetamide.
[0016] Preferably, the oxidant in step S2 is one of dimethyl sulfoxide, copper oxide, copper hydroxide, ferric oxide, and ferric hydroxide.
[0017] Preferably, the solvent in steps S2 and S3 is of the same type and is one of methanol, ethanol, isopropanol, cyclohexane and n-hexane.
[0018] Preferably, the conditions for the electrochemical reaction in step S3 are: the distance between the two electrodes is 0.5 to 2 cm, the DC voltage intensity applied between the two electrodes is 25 to 100 V, and the reaction time is 10 to 30 min.
[0019] Preferably, in step S4, the drying temperature is 60-100° C., and the drying time is 10-30 min.
[0020] The beneficial effects of the present invention are:
[0021] The present invention can realize the electrical stripping of covalent organic framework powder and the electrical deposition of covalent organic framework nanosheets in one step, greatly improving the processability and film-forming property of the covalent organic framework.
[0022] The present invention can improve the hydrophilicity of the membrane and the proton conduction efficiency by electro-depositing a cationic covalent organic framework thin layer on the surface of the perfluorosulfonic acid ion exchange membrane, thereby improving the voltage efficiency of the battery.
[0023] The ionic covalent organic framework thin layer deposited on the surface of the composite membrane prepared by the present invention has regular nano-sized pores with a size of less than 3nm and has obvious positive charge. It can effectively improve the vanadium resistance and ion selectivity of the membrane through the dual effects of size screening and charge repulsion, thereby improving the coulombic efficiency of the battery.
[0024] The ionic covalent organic framework thin layer deposited on the surface of the composite membrane prepared by the present invention is connected to the base membrane through electrostatic attraction, the connection is firm, the modification effect is long-lasting, and the long-term cycle stability of the membrane can be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a schematic diagram of a process flow of a method for preparing a perfluorosulfonic acid-covalent organic framework composite membrane for a vanadium battery according to the present invention;
[0026] Figure 2 The SEM image and XRD image of the covalent organic framework powder in Example 1 of the present invention;
[0027] Figure 3 This is a SEM image of the covalent organic framework nanosheets electro-stripped in Example 2 of the present invention. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below through the accompanying drawings and embodiments. However, it should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the scope of the present invention. In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of the concept of the present invention.
[0029] like Figure 1 As shown, a method for preparing a perfluorosulfonic acid-covalent organic framework composite membrane for a vanadium battery comprises the following steps:
[0030] S1. Add 2 to 10 parts by weight of cationic amine monomers, 3 to 15 parts by weight of aldehyde monomers, 0.5 to 2 parts by weight of catalysts and 100 to 1000 parts by weight of solvents into a reactor, perform ultrasonic dispersion for 10 to 30 minutes, perform solvent thermal reaction at 90 to 120° C. for 24 to 72 hours after nitrogen bubbling and sealing, and obtain a cationic covalent organic framework powder after washing and drying; the cationic amine monomers are selected from triaminoguanidine hydrochloride, ethidium bromide, 1,4-diamino-2-trimethylaminomethoxybenzene hydrochloride, trimethylaminopropoxyterephthaloylhydrazide hydrochloride and 1,1' -bis(4-aminophenyl)-[4,4'-bipyridine]-1,1'-diammonium chloride; the aldehyde monomer is selected from one of 1,3,5-trialdehyde benzene, 2,4,6-tris(4-aldehyde phenyl) pyridine, 2,4,6-trialdehyde pyran, tris(4-aldehyde biphenyl) amine and 2,4,6-tris(4-aldehyde phenyl)-1,3,5-triazine; the catalyst is selected from one of acetic acid solution, trichloroacetic acid and scandium trifluoromethanesulfonate; the solvent is selected from one of deionized water, dioxane, mesitylene, N,N-dimethylformamide and NN-dimethylacetamide;
[0031] S2. Add 0.2 to 2 parts by mass of an oxidant and 0.2 to 2 parts by mass of a solvent to 1 to 15 parts by mass of a covalent organic framework powder, grind in a mortar for 5 to 30 minutes to obtain a slurry, apply the slurry to the surface of a graphite electrode, heat and dry at 60 to 100° C. for 10 to 30 minutes, and then insert the graphite electrode into an electrolytic cell as an anode; fix the finished perfluorosulfonic acid ion exchange membrane on the surface of an indium tin oxide conductive glass, and insert the perfluorosulfonic acid ion exchange membrane into an electrolytic cell as a cathode; the oxidant is one of dimethyl sulfoxide, copper oxide, copper hydroxide, ferric oxide, and ferric hydroxide; the solvent is one of methanol, ethanol, isopropanol, cyclohexane, and n-hexane;
[0032] S3, adding solvent to the electrolytic cell until the liquid level is higher than the two electrodes, applying a DC voltage between the two electrodes, performing an electrochemical reaction, and realizing the electrostripping and electrodeposition of the covalent organic framework in one step; the solvent is the same as that used in step S2; the conditions of the electrochemical reaction are: the distance between the two electrodes is 0.5 to 2 cm, the DC voltage intensity applied between the two electrodes is 25 to 100 V, and the reaction time is 10 to 30 min;
[0033] S4. After the reaction is completed, the membrane is removed from the negative electrode surface, and after cleaning and drying, a perfluorosulfonic acid-covalent organic framework composite membrane is obtained; the drying temperature is 60-100°C, and the drying time is 10-30 minutes.
[0034] Example 1: S1, 20 mg of cationic amine monomer triaminoguanidine hydrochloride, 30 mg of aldehyde monomer 1,3,5-trialdehyde benzene, 5 mg of acetic acid solution and 10 g of deionized water were added to a reactor, ultrasonically dispersed for 10 min, nitrogen bubbled and sealed, and then solvothermally reacted at 90° C. for 48 h, and then washed and dried to obtain an ionic covalent organic framework powder;
[0035] S2, add 2 mg of dimethyl sulfoxide and 2 g of methanol to 10 mg of the covalent organic framework powder in step S1, grind in a mortar for 5 min to obtain a slurry, apply the slurry to the surface of a graphite electrode, heat and dry at 60° C. for 10 min, and then insert the graphite electrode into an electrolytic cell as an anode; fix the finished perfluorosulfonic acid ion exchange membrane on the surface of an indium tin oxide conductive glass, and insert the slurry into the electrolytic cell as a cathode;
[0036] S3, add methanol to the electrolytic cell until the liquid level is higher than the two electrodes, the distance between the two electrodes is 0.5cm, apply a DC voltage of 25V between the two electrodes, and the power-on time is 3h;
[0037] S4. After the reaction is completed, the membrane is removed from the negative electrode surface, washed with pure water and ethanol, and dried at 60°C for 10 minutes to obtain a perfluorosulfonic acid-covalent organic framework composite membrane.
[0038] Example 2: S1, 40 mg of cationic amine monomer ethidium bromide, 60 mg of aldehyde monomer 2,4,6-tris(4-formylphenyl)pyridine, 10 mg of trifluoroacetic acid and 30 g of dioxane were added to a reaction kettle, ultrasonically dispersed for 20 min, nitrogen bubbled and sealed, and then solvothermally reacted at 100° C. for 24 h, and then washed and dried to obtain an ionic covalent organic framework powder;
[0039] S2, add 10 mg of copper oxide and 5 g of ethanol to 30 mg of the covalent organic framework powder in step S1, grind in a mortar for 10 min to obtain a slurry, apply the slurry to the surface of a graphite electrode, heat and dry at 70° C. for 15 min, and then insert the graphite electrode into an electrolytic cell as an anode; fix the finished perfluorosulfonic acid ion exchange membrane on the surface of an indium tin oxide conductive glass, and insert the slurry into the electrolytic cell as a cathode;
[0040] S3, add ethanol to the electrolytic cell until the liquid level is higher than the two electrodes, the distance between the two electrodes is 1 cm, and a DC voltage of 50V is applied between the two electrodes for 2 hours;
[0041] S4. After the reaction is completed, the membrane is removed from the negative electrode surface, washed with pure water and ethanol, and dried at 70°C for 15 minutes to obtain a perfluorosulfonic acid-covalent organic framework composite membrane.
[0042] Example 3: S1, 60 mg of cationic amine monomer 1,4-diamino-2-trimethylaminomethoxybenzene hydrochloride, 90 mg of aldehyde monomer 2,4,6-trialdehyde pyran, 15 mg of acetic acid and 50 g of mesitylene were added to a reactor, ultrasonically dispersed for 30 min, and then nitrogen bubbled and sealed at 110° C. for solvent thermal reaction for 72 h. After washing and drying, an ionic covalent organic framework powder was obtained;
[0043] S2, add 20 mg of copper hydroxide and 10 g of isopropanol to 50 mg of the covalent organic framework powder in step S1, grind in a mortar for 15 min to obtain a slurry, apply the slurry to the surface of a graphite electrode, heat and dry at 80° C. for 20 min, and then insert the graphite electrode into an electrolytic cell as an anode; fix the finished perfluorosulfonic acid ion exchange membrane on the surface of an indium tin oxide conductive glass, and insert the slurry into the electrolytic cell as a cathode;
[0044] S3. Add isopropanol to the electrolytic cell until the liquid level is higher than the two electrodes. The distance between the two electrodes is 1.5 cm. Apply a DC voltage of 100 V between the two electrodes for 0.5 h.
[0045] S4. After the reaction is completed, the membrane is removed from the negative electrode surface, washed with pure water and ethanol, and dried at 80°C for 20 minutes to obtain a perfluorosulfonic acid-covalent organic framework composite membrane.
[0046] Example 4: S1, 80 mg of cationic amine monomer trimethylaminopropoxy terephthaloyl hydrazide hydrochloride, 120 mg of aldehyde monomer tris (4-formyl biphenyl) amine, 10 mg of scandium trifluoromethanesulfonate and 75 g of N, N-dimethylformamide were added to a reactor, ultrasonically dispersed for 20 min, nitrogen bubbled and sealed, and then solvothermally reacted at 120 ° C for 60 h, and then washed and dried to obtain an ionic covalent organic framework powder;
[0047] S2, add 15 mg of ferric oxide and 15 g of cyclohexane to 100 mg of the covalent organic framework powder in step S1, grind in a mortar for 20 min to obtain a slurry, apply the slurry to the surface of a graphite electrode, heat and dry at 90° C. for 25 min, and then insert the graphite electrode into an electrolytic cell as an anode; fix the finished perfluorosulfonic acid ion exchange membrane on the surface of an indium tin oxide conductive glass, and insert the slurry into the electrolytic cell as a cathode;
[0048] S3. Add cyclohexane to the electrolytic cell until the liquid level is higher than the two electrodes. The distance between the two electrodes is 2 cm. Apply a DC voltage of 75 V between the two electrodes for 1 hour.
[0049] S4. After the reaction is completed, the membrane is removed from the negative electrode surface, washed with pure water and ethanol, and dried at 90°C for 25 minutes to obtain a perfluorosulfonic acid-covalent organic framework composite membrane.
[0050] Example 5: S1, 100 mg of cationic amine monomer 1,1'-bis(4-aminophenyl)-[4,4'-bipyridine]-1,1'-diammonium chloride, 150 mg of aldehyde monomer 2,4,6-tris(4-formylphenyl)-1,3,5-triazine, 20 mg of acetic acid and 100 g of N.N-dimethylacetamide were added to a reaction kettle, ultrasonically dispersed for 10 min, and then nitrogen bubbled and sealed at 100° C. for solvent thermal reaction for 36 h. After washing and drying, an ionic covalent organic framework powder was obtained;
[0051] S2, add 10 mg of ferric hydroxide and 20 g of n-hexane to 150 mg of the covalent organic framework powder in step S1, grind in a mortar for 30 min to obtain a slurry, apply the slurry to the surface of a graphite electrode, heat and dry at 100° C. for 30 min, and then insert the graphite electrode into an electrolytic cell as an anode; fix the finished perfluorosulfonic acid ion exchange membrane on the surface of an indium tin oxide conductive glass, and insert the slurry into the electrolytic cell as a cathode;
[0052] S3. Add n-hexane to the electrolytic cell until the liquid level is higher than the two electrodes. The distance between the two electrodes is 1 cm. Apply a DC voltage of 50 V between the two electrodes for 2.5 hours.
[0053] S4. After the reaction is completed, the membrane is removed from the negative electrode surface, washed with pure water and ethanol, and dried at 100°C for 30 minutes to obtain a perfluorosulfonic acid-covalent organic framework composite membrane.
[0054] Comparative Example 1: The perfluorosulfonic acid membrane was immersed in methanol for 3 hours, washed with pure water and ethanol, and then dried at 60° C. for 10 minutes.
[0055] Comparative Example 2: Replace the cationic amine monomer ethidium bromide in Example 2 with an anionic amine monomer 2,5-diaminobenzenesulfonic acid. The specific steps are: S1, add 40 mg of anionic amine monomer 2,5-diaminobenzenesulfonic acid, 60 mg of aldehyde monomer 2,4,6-tris(4-formylphenyl)pyridine, 10 mg of trifluoroacetic acid and 30 g of dioxane into a reactor, ultrasonically disperse for 20 min, and then perform solvent thermal reaction at 100°C for 24 h after nitrogen bubbling and sealing, and then wash and dry to obtain an ionic covalent organic framework powder;
[0056] S2, add 10 mg of copper oxide and 5 g of ethanol to 30 mg of the covalent organic framework powder in step S1, grind in a mortar for 10 min to obtain a slurry, apply the slurry to the surface of a graphite electrode, heat and dry at 70° C. for 15 min, and then insert the graphite electrode into an electrolytic cell as a cathode; fix the finished perfluorosulfonic acid ion exchange membrane on the surface of an indium tin oxide conductive glass, and insert the slurry into the electrolytic cell as an anode;
[0057] S3, add ethanol to the electrolytic cell until the liquid level is higher than the two electrodes, the distance between the two electrodes is 1 cm, and a DC voltage of 50V is applied between the two electrodes for 2 hours;
[0058] S4. After the reaction is completed, the membrane is removed from the negative electrode surface, washed with pure water and ethanol, and dried at 70°C for 15 minutes to obtain a perfluorosulfonic acid-covalent organic framework composite membrane.
[0059] 1. Characterization of the morphology of covalent organic framework powder and nanosheets: Take a small amount of covalent organic framework powder and stick it on the conductive glue and stick it on the electron microscope stage; after the power is turned on in step S3, the covalent organic framework nanosheet dispersion is centrifuged, the upper clear liquid is dropped on the surface of the anodized aluminum oxide (AAO) base film, and it is stuck on the electron microscope stage through the conductive glue.
[0060] 2. Characterization of the structural regularity of the covalent organic framework powder: Take a small amount of the covalent organic framework powder for powder X-ray diffraction (PXRD) characterization at an angle of 2-40°.
[0061] 3. Battery performance test: The membranes in Examples 1-5 and Comparative Examples 1-2 were assembled into battery stacks for testing.
[0062] The coulombic efficiency, voltage efficiency and energy efficiency were tested and recorded under the same working conditions. The test results are shown in Table 1:
[0063] Table 1 Battery performance test results
[0064]
[0065] Figure 2(a) is a SEM image of the covalent organic framework powder prepared in Example 1. It can be seen that the covalent organic framework powder prepared in Example 1 has a morphology in which particles and fibers coexist. Figure 2 (b) is the XRD pattern of the covalent organic framework powder prepared in Example 1, showing that in the XRD pattern of the powder, there are obvious characteristic diffraction peaks at ~10° and ~27°, corresponding to the (100) and (001) crystal planes of its crystal, respectively, indicating that it has good structural regularity and also provides a basis for the subsequent electro-stripping to prepare highly crystalline nanosheets.
[0066] Figure 3 This is a SEM image of the covalent organic framework nanosheets electrostripped in Example 2 of the present invention. It can be seen that the covalent organic framework nanosheets electrostripped in Example 2 have a complete and continuous layered structure, and its size reaches several microns. The aluminum oxide substrate below can still be seen through the nanosheets, indicating that its thickness is relatively thin, and the electrostripping effect assisted by a weak oxidant is better. It can be seen that the present invention can achieve the electrostripping of covalent organic framework powder and the electrodeposition of covalent organic framework nanosheets in one step, greatly improving the processability and film-forming properties of the covalent organic framework.
[0067] It can be seen from Table 1 that the comprehensive performance indicators of the membranes in Examples 1-5 are significantly higher than those of the blank membrane in Comparative Example 1, indicating that the electrodeposited covalent organic framework thin layer can greatly enhance the performance of the perfluorosulfonic acid membrane. Specifically, compared with the blank perfluorosulfonic acid membrane in Comparative Example 1, the voltage efficiency of Example 1 is improved, indicating that the electrodeposition of an ionic covalent organic framework thin layer on the surface of the perfluorosulfonic acid ion exchange membrane can improve the hydrophilicity of the membrane, improve the proton conduction efficiency, and thus improve the voltage efficiency of the battery. At the same time, in the long-term cycle test, the membranes prepared in Examples 1-5 showed a higher capacity retention rate after 150 cycles than the blank membrane in Comparative Example 1, indicating that the covalent organic framework layer is firmly connected to the perfluorosulfonic acid membrane, the modification effect is long-lasting, and the long-term cycle stability of the membrane can be improved. Comparative Example 2 replaces the cationic amine monomer used in Example 2 with anionic amine monomers, that is, a negatively charged covalent organic framework thin layer is deposited on the surface of the perfluorosulfonic acid membrane. Compared with the blank membrane in Comparative Example 1, the coulombic efficiency can also be improved. This is because the smaller pore size brings higher vanadium resistance, but lacks the charge repulsion effect with vanadium ions, resulting in its ion selectivity being inferior to that of Comparative Example 2, and the performance improvement is also inferior. This shows that the present method can effectively improve the vanadium resistance and ion selectivity of the membrane through the dual effects of size screening and charge repulsion, thereby improving the coulombic efficiency of the battery.
[0068] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a perfluorosulfonic acid-covalent organic framework composite membrane for a vanadium battery, characterized in that: The steps include: S1, 2-10 parts by weight of cationic amine monomers, 3-15 parts by weight of aldehyde monomers, 0.5-2 parts by weight of catalysts and 100-1000 parts by weight of solvents are added to a reactor, ultrasonically dispersed for 10-30 minutes, nitrogen bubbled and sealed, solvent thermally reacted at 90-120° C. for 24-72 hours, and then washed and dried to obtain a cationic covalent organic framework powder; the cationic amine monomers are selected from triaminoguanidine hydrochloride, ethidium bromide, 1,4-diamino -2-trimethylaminomethoxybenzene hydrochloride, trimethylaminopropoxyterephthaloylhydrazide hydrochloride and 1,1'-bis(4-aminophenyl)-[4,4'-bipyridine]-1,1'-diammonium chloride; the aldehyde monomer is selected from 1,3,5-trialdehyde benzene, 2,4,6-tris(4-aldehyde phenyl) pyridine, 2,4,6-trialdehyde pyran, tris(4-aldehyde biphenyl) amine and 2,4,6-tris(4-aldehyde phenyl)-1,3,5-triazine; S2. Add 0.2 to 2 parts by mass of a weak oxidant and 0.2 to 2 parts by mass of a solvent to 1 to 15 parts by mass of a covalent organic framework powder, grind in a mortar for 5 to 30 minutes to obtain a slurry, apply the slurry to the surface of a graphite electrode, heat and dry at 60 to 100° C. for 10 to 30 minutes, and then insert the graphite electrode into an electrolytic cell as an anode; fix the finished perfluorosulfonic acid ion exchange membrane on the surface of an indium tin oxide conductive glass, and insert the slurry into the electrolytic cell as a cathode; S3, adding solvent to the electrolytic cell until the liquid level is higher than the two electrodes, applying a DC voltage between the two electrodes, performing an electrochemical reaction, and realizing the electrostripping and electrodeposition of the covalent organic framework in one step; the conditions of the electrochemical reaction are: the distance between the two electrodes is 0.5 to 2 cm, the DC voltage intensity applied between the two electrodes is 25 to 100 V, and the reaction time is 10 to 30 min; S4. After the reaction is completed, the membrane is removed from the negative electrode surface, and after cleaning and drying, a perfluorosulfonic acid-covalent organic framework composite membrane is obtained.
2. The method for preparing a perfluorosulfonic acid-covalent organic framework composite membrane for vanadium batteries according to claim 1, characterized in that: In step S1, the catalyst is selected from one of acetic acid solution, trichloroacetic acid and scandium trifluoromethanesulfonate.
3. The method for preparing a perfluorosulfonic acid-covalent organic framework composite membrane for vanadium batteries according to claim 1, characterized in that: In step S1, the solvent is selected from one of deionized water, dioxane, mesitylene, N,N-dimethylformamide and NN-dimethylacetamide.
4. The method for preparing a perfluorosulfonic acid-covalent organic framework composite membrane for vanadium batteries according to claim 1, characterized in that: In step S2, the weak oxidant is one of dimethyl sulfoxide, copper oxide, copper hydroxide, ferric oxide, and ferric hydroxide.
5. The method for preparing a perfluorosulfonic acid-covalent organic framework composite membrane for vanadium batteries according to claim 1, characterized in that: The solvent in steps S2 and S3 is of the same type and is one of methanol, ethanol, isopropanol, cyclohexane and n-hexane.
6. The method for preparing a perfluorosulfonic acid-covalent organic framework composite membrane for vanadium batteries according to claim 1, characterized in that: In step S4, the drying temperature is 60-100° C. and the drying time is 10-30 minutes.
Citation Information
Patent Citations
Electrodeposition preparation method and application of ionic covalent organic framework nanosheet protective layer
CN115010941A
Method for electrochemically preparing covalent organic framework composite membrane and application of covalent organic framework composite membrane
CN115105971A